Actual body weight-based vancomycin dosing in neonates - Pokorná, Pavla; Šíma, Martin; Černá, Olga; Allegaert, Karel; Tibboel, Dick; Slanař, Ondřej (Journal of chemotherapy, 2019)
This study aimed to explore vancomycin pharmacokinetics and its covariates in critically ill neonates and to propose an easy applicable dosing nomogram for initial treatment. Individual vancomycin pharmacokinetic parameters were calculated based on therapeutic drug monitoring data using a one-compartmental model. A linear regression model was used for examination of covariates. The mean (SD) volume of distribution (Vd) and clearance (CL) for vancomycin were 0.73 (0.31) L/kg and 0.052 (0.020) L/h/kg, respectively. Vd was related to actual body weight (ABW), gestational and postmenstrual age. CL was also associated with ABW, gestational, postmenstrual age and also creatinine clearance. ABW was the strongest predictor for vancomycin pharmacokinetics and consequently dosing. Loading dose (mg) of 11.81 × ABW (kg) + 7.86 and maintenance dose (mg/day) of 40.92 × ABW (kg) -22.18 most closely approximated pharmacokinetic target. Vancomycin pharmacokinetics was mainly influenced by ABW in neonates and a practical ABW-based dosing algorithm was developed.
Keywords: Nomograms; novorozenec; Infant, Newborn; vankomycin; Drug Monitoring; Humans; Sepsis; monitorování léčiv; Female; sepse; lidé; antibakteriální látky; nomogramy; Vancomycin; ženské pohlaví; Anti-Bacterial Agents; Male; Body Weight; tělesná hmotnost; mužské pohlaví